Optical data related to Ag nanoplates utilized for plasmon sensing - Condorelli, Marcello (Data Brief, 2019)
In this data paper we share the absorption spectrum of Ag NP ablated in pure water and in presence of trisodium citrate (TSC). We also share the full emission spectrum of the irradiation lamp used for the reshaping process described in the related research paper. The data is related to the research article “Plasmon Sensing and enhancement of laser prepared silver colloids” [1].